The Effect Of Thermal Oxidation On Monocrystalline Silicon Solar Cell Efficiency - Wahab, Nursaniyah A (2013)
This thesis focuses on fabricating monocrystalline silicon solar cell and highlights the surface passivation on the front and back surface of the cell. The main objective of this work is to develop and optimize a process for the fabrication of silicon solar cell. Special attention has been paid to find the optimum thickness of dry oxidation process for front surface passivation with thermally grown silicon oxide (SiO) layers has been investigated for comparison. New technique for interpreting the front surface passivation layer is by introducing both dry and wet oxidation process to form the oxide layer. In addition, the effect of photocurrent response to oxide thickness is studied using SILVACO software. The rear surface passivation properties with optimised Al-BSF films have been extensively studied over a large range of resistivity. The resistivity decreases after the formation of Al-BSF from ~6.05 Ω.cm to ~1.81 Ω.cm for all the cells. It was observed that the cell with no surface passivation gives the lowest output value with Voc = 383 mV, Isc = 5.25 mA and the efficiency only 0.29%. The best cell with oxide thickness of 905 Å gives the highest efficiency value which is 4.02% and the Voc = 468 mV, Isc = 24.70 mA. The values were tested using solar simulator system under 270 W/m2 illumination with cell area = 4.7 cm2 under AM1.5 at 25 °C.